Economic and financial feasibility of a diversified market farm in west Michigan - Whittington, Steve (Kansas State University, 2022)
Market farming has become a popular style of farming for young and beginning farmers who desire to start their own agribusiness operation. Recent research has shown that market farming can be profitable, but the initial capital requirements and net returns need to be quantified in order to assess financial feasibility. Front Porch Farms is a beginning market farm which is assessing the financial feasibility of beginning a market farming operation in West Michigan. A capital budget was created listing all required equipment, materials, and infrastructure to begin an operation and produce a marketable product. Enterprise budgets were created for a core group of five popular direct market crops: carrots, greens mixes, head lettuce, sweet peppers, and heirloom tomatoes. Production costs were estimated by analyzing the labor, material, and marketing costs associated with producing each of the crops on a 30’’ by 50’ bed system. The net returns with this standardized unit of production were then estimated with both an optimistic and pessimistic year one net return. The optimistic and pessimistic year one return on investment and payback period was calculated. The year one return on investment is 45.19% with a pessimistic analysis of net returns and 126% with optimistic net returns. The payback period for year one with a pessimistic analysis of net returns is 2.21 years and 0.78 years with an optimistic analysis. Through the analysis, the owners determined that with the net return on investment and sufficient payback period, investment of capital into a market farm will be conducted.
Keywords: Market farm; Agribusiness; Farm to fork; Profitability; Feasibility